Effect of area-level socioeconomic deprivation on mental and physical health: a longitudinal natural experiment among refugees in Germany - Biddle, Louise; Bozorgmehr, Kayvan (SSM - population health, 2024)
Existing studies on contextual health effects struggle to account for compositional bias, limiting causal interpretation. We use refugee dispersal in Germany as a natural experiment to study the effect of area-level socioeconomic deprivation on mental and physical health, while considering the potential mediating role of neighbourhood characteristics. Refugees subject to dispersal (n = 1466) are selected from a nation-wide longitudinal refugee study (IAB-SOEP-BAMF Panel; 2016-2018). Multi-level linear regression models, adjusted for age, sex, education, country of origin, federal state, asylum status and length of residence in Germany, are fitted to the change in mental and physical health subscales of the SF-12 depending on quintiles (Q1 - Q5) of commune-level socioeconomic deprivation (German Index of Socioeconomic Deprivation, GISD). This is followed by sensitivity analyses and mediation analyses for housing, social cohesion, proportion of non-citizens in the neighbourhood, access to green space, population density and primary care physician density. Residency in districts with moderate-high deprivation (Q4) has a negative impact on physical health (coef.: -2.2, 95%CI: -4.1;-0.2) compared to lowest deprivation (Q1). Moderate-high deprivation (Q4) has a positive impact on mental health, but the effect is statistically insignificant (coef.: 1.6, 95%CI: -0.7; 3.9). Comparisons with other deprivation quintiles are statistically insignificant. Sensitivity analyses confirm results of the final models, while no mediating factors show a substantial impact on the observed relationship. The results point to gaps in health and social service provision for refugees living in the most deprived regions, but further research is required to understand the precise mechanisms behind the observed relationships. Further research using longer timeframes and larger sample sizes are required to confirm results.
Online verfügbar: 2. Januar 2024, Artikelversion: 25. Januar 2024
Gesehen am 19.07.2024